Programmed Death-1/Programmed Death-Ligand 1-Axis Blockade in Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma Stratified by Human Papillomavirus Status: A Systematic Review and Meta-Analysis - Xu, Yimin; Zhu, Gangcai; Maroun, Christopher A.; Wu, Irene X. Y.; Huang, Donghai; Seiwert, Tanguy Y.; Liu, Yong; Mandal, Rajarsi; Zhang, Xin (Frontiers in Immunology, 2021)
Background: Programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors have provided clinical benefit to head and neck squamous cell carcinoma (HNSCC) patients in recent clinical trials. However, it remains unclear as to whether human papillomavirus (HPV) status is associated with improved clinical outcome of anti-PD-1 or anti-PD-L1 immunotherapy in HNSCC. Methods: PubMed, EMBASE, Cochrane Library, and Web of Science were systematically searched up to February 28, 2021. Published clinical trials of HNSCC patients treated with only PD-1 or PD-L1 inhibitors were selected. The primary or secondary outcome of these studies included objective response rate (ORR) stratified by HPV status. The pooled odds ratio (OR) and hazard ratio (HR) were estimated using a fixed-effect model. Results: A total of seven eligible studies comprising 814 patients were included. The ORR of HPV positive HNSCC patients was significantly higher than that of HPV negative HNSCC patients (OR = 1.77; 95%CI = 1.14-2.74; P = 0.01), and this favorable effect occurred in pooled anti-PD-L1 trials (OR = 2.66; 95%CI = 1.16-6.11; P = 0.02). In comparison, the pooled OR was 1.51 in anti-PD-1 trials (95%CI = 0.90-2.54; P = 0.12). Survival analysis indicated that HPV positive HNSCC patients had a lower risk of overall death as compared to HPV negative HNSCC patients (HR = 0.77; 95%CI = 0.60–0.99; P = 0.04). Conclusions: HPV positive HNSCC patients display improved outcomes with PD-1/PD-L1 axis blockade as compared to HPV negative HNSCC patients. These improved outcomes are likely driven to a greater extent by anti-PD-L1 inhibitors. However, randomized controlled trials with greater numbers of patients are needed for validation of these early findings.